The contributions of managed care plans to public health practice: evidence from the nation's largest local health departments. - Mays, G. P. (2001)
OBJECTIVE: The authors examine the extent and nature of managed care plans participating in local public health activities. METHODS: In 1998, the authors surveyed the directors of all US local health departments serving jurisdictions of at least 100,000 residents to collect information about public health activities performed in their jurisdictions and about organizations participating in the activities. Multivariate logistic and linear regression models were used to examine organizational and market characteristics associated with managed care plan participation in public health activities. RESULTS: Managed care plans were reported to participate in public health activities in 164 (46%) of the jurisdictions surveyed, and to contribute to 13% of the public health activities performed in the average jurisdiction. Plans appeared most likely to participate in public health activities involving the delivery or management of personal health services and the exchange of health-related information. Managed care participation was more likely to occur in jurisdictions with higher HMO penetration, fewer competing plans, and larger proportions of plans enrolling Medicaid recipients. Participation was positively associated with the overall scope and perceived effectiveness of local public health activities. CONCLUSIONS: Although plans participate in a narrow range of activities, these contributions may complement the work of public health agencies.